Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns - Roy, Devesh; Kamar, Abul; Pradhan, Mamata; Saroj, Sunil; Ajmani, Manmeet Singh (International Food Policy Research Institute, 2023)
In this paper, we address the question of the agricultural market integration of Cambodia, Lao, Myanmar, Vietnam, and Philippines (CLMVP) countries within the Association of Southeast Asian Nations (ASEAN), and its other top trading partners. Using “Trade Potential” and “Competition Indices” indicators in this paper we assess the nature and extent of the agricultural market integration. We identify the exports of CLMVP countries with high export potential and comparatively low competition in export markets. Higher trade potential with lower competition (value or volume) indicates an opportunity of higher returns for agricultural producers. CLMVP countries are characterized by low diversity in agricultural exports. Nearly half of the total agricultural exports from all of them except Laos is contributed by only one commodity. It is found that market integration is an effective way of linking CLMVP smallholders to ASEAN agricultural markets. In addition to that this paper also discusses on tariff and non-tariff policy of CLMVP countries and found that the average tariffs on agri-food imports in CLMVP is 11.8% while it is 9.5% in non-CLMVP among the ASEAN countries. In non-tariff policy, among the CLMVP countries, Philippines shares the maximum number of SPS measures implemented on agricultural goods while Cambodia and Lao PDR did not report any SPS measures implemented by them between 2006 to 2020. Finally, to demonstrate the upward movement in the value chain, possibly due to quality upgradation, we present the dynamics of the unit values of CLMVP’s agricultural exports.